2017
DOI: 10.1080/03098265.2017.1331209
|View full text |Cite
|
Sign up to set email alerts
|

Developing trainee teacher practice with geographical information systems (GIS)

Abstract: There is general agreement that Geographical Information Systems (GIS) have a place within the geography classroom; they offer the potential to support geographical learning, exploring real-world problems through student-centred learning, and developing spatial thinking. Despite this, teachers often avoid engaging with GIS and research suggests that the lack of GIS training in initial teacher education is partially to blame. In response to this, this article explores how 16 trainee geography teachers were supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…Finally, extensive feedback and coaching, from improving classroom delivery to growing teacher confidence in using some of the more powerful features of DE tools when teaching their students, is a necessary support. Importantly, these findings are supported by work with educators across many countries, including Germany (Hohnle et al 2016), the United States (Mitchell et al 2018), the United Kingdom (Walshe 2017), and Hong Kong, China (Lam et al 2009), suggesting that common teacher-training approaches in DE could be useful. A well-trained teacher corps that is mindful of how DE can be deployed in pedagogically appropriate ways (Mishra and Koehler 2006) can lead to a student population ready to connect DE technology with a problem-focused approach to learning.…”
Section: Digital Earth For K-12mentioning
confidence: 74%
See 1 more Smart Citation
“…Finally, extensive feedback and coaching, from improving classroom delivery to growing teacher confidence in using some of the more powerful features of DE tools when teaching their students, is a necessary support. Importantly, these findings are supported by work with educators across many countries, including Germany (Hohnle et al 2016), the United States (Mitchell et al 2018), the United Kingdom (Walshe 2017), and Hong Kong, China (Lam et al 2009), suggesting that common teacher-training approaches in DE could be useful. A well-trained teacher corps that is mindful of how DE can be deployed in pedagogically appropriate ways (Mishra and Koehler 2006) can lead to a student population ready to connect DE technology with a problem-focused approach to learning.…”
Section: Digital Earth For K-12mentioning
confidence: 74%
“…Successful teacher implementation requires long-term support instead of one-time PD. For example, Walshe (2017) showed that pre-service geography teachers with "gradual yet repeated exposure to GIS with increasing complexity across the [school] year" better developed their practice. Professional learning communities also sustain DE use.…”
Section: Digital Earth For K-12mentioning
confidence: 99%
“…Logistical and technological barriers to using GIS with students are well acknowledged (e.g. Hong & Stonier, 2015) and although such barriers have been diminishing in recent years (Fargher, 2017a) it is still perceived that teachers are hesitant to engage with GIS (Hong, 2017;Walshe, 2017). Walshe (2018) posits an alternative barrier, suggesting that teachers trying to overcome difficulties associated with technology may be detracting from, rather than enhancing, geographical learning; further consideration for how GIS can yield greater capacity for geographical thinking in students is needed to overcome this.…”
Section: The School Curriculum and Student Engagement With Gismentioning
confidence: 99%
“…The value of GIS in geography education has been well established (Bednarz, 2004), with GIS being used successfully in "promoting spatial literacy; supplementing fieldwork and in enhancing pupils' visualisations of geographical phenomena in increasingly interactive digital environments often through geographical enquiry" (Fargher, 2017a, p.151). While GIS is increasingly being seen in school geography classrooms (Bednarz, 2004), there remains significant reluctance among teachers to engage with the technology (Hong, 2017;Walshe, 2017), as well as relatively little evidence to consider students' responses to it. In answer to this, we are undertaking longitudinal research to explore how a programme of GIS training, integrated within a two-year A-Level examination course, develops students' perceptions of the value and nature of GIS, their subsequent engagement with it, and its impact on their geographical knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…The cost of GIS training for personnel tends to be high, both due to the steep learning curve associated with the software and statistical methods needed and to the common shortage of experienced instructors (Delmelle et al, 2001;Schuurman et al, 2008;Walshe, 2017). The literature on primary care personnel training for electronic devices argues that training is often financially inefficient and commonly produces errors (Wang et al, 2003).…”
Section: Shortage Of Technical Capacity and Trained Personnelmentioning
confidence: 99%